COLLABORATIONS WITH NIGERIAN EDUCATIONAL INSTITUTIONS TO BE INCREASED - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – Emphasis should be given on the need to share knowledge and expertise at the global level, as well as cooperation between educational institutions and their partners to ensure a future for the betterment of all.